Is Criminology a Policy Science - Geis, Gilbert (1977)
The question posed in the title is discussed in view of selected evidence from the criminological literature. Criminology's status as a policy science, based largely on the ability of the discipline to present coherent, empirically-based recommendations for the reduction of crime, is evaluated. The review leads to disappointing conclusions with respect to the usefulness to policymakers of the present knowledge base in criminology